[Payment to Ah Louis from John S. Luis] - John S. Luis::::::::: (1885)
Payment, in the amount of $40.00, to Ah Louis from John S. Lewis for Chinese woodchoppers. This is possibly the envelope for the object with the identifier 167-7-d-29-09-03.